2018
DOI: 10.1002/adma.201704611
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Powered and Flexible Organometallic Halide Perovskite Photodetector with Very High Detectivity

Abstract: Flexible and self-powered photodetectors (PDs) are highly desirable for applications in image sensing, smart building, and optical communications. In this paper, a self-powered and flexible PD based on the methylammonium lead iodide (CH NH PBI ) perovskite is demonstrated. Such a self-powered PD can operate even with irregular motion such as human finger tapping, which enables it to work without a bulky external power source. In addition, with high-quality CH NH PBI perovskite thin film fabricated with solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
236
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(242 citation statements)
references
References 41 publications
3
236
0
Order By: Relevance
“…[22] Compared to the homogeneously doped BiVO 4 , the continuous built-in band bending induces the directional transfer of photogenerated holes from core to surface and thus increases the carrier separation efficiency to 60%. Apart from the integrated system with an energy conversion or harvester unit, [5][6][7] the perovskite photodiode is an excellent alternative in terms of simple structure, light weight, and portability. [23] We reported graded CdS x Se 1-x nanobelt solar cells by utilizing continuous stepped energy levels to drive electrons and holes toward opposite direction.…”
mentioning
confidence: 99%
“…[22] Compared to the homogeneously doped BiVO 4 , the continuous built-in band bending induces the directional transfer of photogenerated holes from core to surface and thus increases the carrier separation efficiency to 60%. Apart from the integrated system with an energy conversion or harvester unit, [5][6][7] the perovskite photodiode is an excellent alternative in terms of simple structure, light weight, and portability. [23] We reported graded CdS x Se 1-x nanobelt solar cells by utilizing continuous stepped energy levels to drive electrons and holes toward opposite direction.…”
mentioning
confidence: 99%
“…Organic–inorganic lead halide perovskites have recently been intensively investigated due to their superior optoelectronic and photovoltaic characteristics. Since their pioneering application in solar cells with an efficiency of 3.8% in 2009, researchers have made great efforts to further develop metal halide perovskites in various applications such as field‐effect transistors, solar cells, photodetectors, thermoelectrics, tandem devices, light‐emitting electrochemical cells, diodes, and laser . Despite the rapid growth of the organic–inorganic lead halide perovskite research efforts in both academia and industry, two biggest challenges still remain and hinder their widespread applications.…”
mentioning
confidence: 99%
“…As shown in Figure c, the data can be transferred directly to a smart mobile device using an antenna and a batteryless NFC chip with a small built‐in CPU capable of data processing. Leung et al reported a photodetector integrated with triboelectric nanogenerators (TENGs), which are batteryless, flexible, and transparent . The device exploits halide‐structured methylammonium lead iodide (CH 3 NH 3 PBI 3 ) perovskite, which enabled high detectivity, flexibility, and transparency, thus enabling compatibility to a wearable platform.…”
Section: Advanced Applications Of Smart Sensing Systems Based On Optomentioning
confidence: 99%
“…e) Characteristics of the perovskite photodetector which present the photocurrent and responsivity under a variety of intensities of light. d,e) Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Advanced Applications Of Smart Sensing Systems Based On Optomentioning
confidence: 99%